Wellbeing in Mamelodi: community engagement, social support and mental health in Kasi (township) South Africa - Malope, Seemela Desiree (My University, 2021)
Although a vital part of wellbeing, poor mental health and mental illnesses in low-income areas are not treated the same way as other illnesses. Unlike acute illnesses that are usually responded to with urgency, mood disorders and other mental illnesses generally do not include physical symptoms, and they are therefore more likely to be ignored, disregarded or dismissed. How people understand and respond to mental health crises are influenced by whether or not they are also encountering major difficulties within the family and/or community, or threats to the family and/or community, due to deficient resources such as healthcare, low income, and lack of knowledge on mental health. In addition, considerable stigma is still attached to mental illnesses, often reflecting people’s lack of knowledge but also their discomfort with people who are emotionally labile, incoherent or confused. This makes addressing mental health issues particularly challenging. This study is located in a poor urban area which I refer to as Kasi. Focusing on one community organisation, I look at the role of community engagement in supporting individual wellbeing and addressing mental health in Kasi. Data were collected through focus group discussions and in-depth interviews with people belonging to a contemporary community group, with both focus groups and interviews hosted via WhatsApp over a period of three months. The data gathered through these methods indicated the benefits and advantages of belonging to and participating in community organisations; participants recalled personal experiences of belonging to the group, elaborating on how wellbeing is defined, and explained how mental health and mental illnesses are perceived in Kasi. The findings in this study suggest the need for further research to examine and analyse notions about mental health which make it difficult for individuals, families and health professionals to address mental health issues in low-income settings. The findings also suggest the value of looking further into the power of community engagement in enhancing wellbeing within marginalised groups
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021